Knowledge, attitude, and practice regarding obstructive sleep apnea among primary care physicians - Devaraj, Navin Kumar (Springer, 2020)
Purpose: Obstructive sleep apnea (OSA) has been linked with inflammation, hypertension, and higher cardiovascular risk which cause substantial morbidity and mortality worldwide. However, OSA is underdiagnosed and its prevalence is increasing. Primary care doctors are the first contact for most patients and primary care providers play an important role in promoting, screening, and educating patients regarding OSA. This study aims to determine the knowledge, attitudes, and practices regarding OSA among primary care doctors in Kuala Lumpur, Malaysia. Methods: A cross-sectional survey was conducted among physicians who were currently working in primary care clinics in the capital state of Kuala Lumpur. The validated "Obstructive Sleep Apnea Knowledge and Attitudes Questionnaire" (OSAKA) and nine additional practice questions were used as the survey instrument. Results: Of 207 physicians queried, the response rate was 100%. The mean (± SD) total knowledge score was 11.6 (± 2.8) (range 1-18). The majority of respondents had a positive attitude towards the importance of OSA but lacked confidence in managing OSA. Primary care doctors' most common practice for patients with suspected OSA was referral to the ear, nose, and throat (ENT) clinic. Conclusions: The study shows that primary care doctors demonstrated adequate knowledge about OSA and were aware of the importance of OSA as a core clinical problem. However, only a minority felt confident in managing patients with OSA. The results of the study may encourage improvement of primary care doctors' efforts to prevent and manage OSA.